A systematic review: The role of emerging carbon capture and conversion technologies for energy transition to clean hydrogen - Sadah Mohammed (18192859) (2024)
The exploitation of fossil fuels in various sectors, such as power and heat generation, and the transportation sector has been the primary source of greenhouse gas (GHG) emissions, which are the main contributors to global warming. Qatar's oil and gas sector notably contributes to CO2 emissions, accounting for half of the total emissions. Globally, it is essential to transition into cleaner fossil fuel production to achieve carbon neutrality on a global scale. In this paper, we focus on clean hydrogen, considering carbon capture to make hydrogen a viable low carbon energy alternative for the transition to clean energy. This paper systematically reviews emerging technologies in carbon capture and conversion (CCC). First, the road map stated by the Intergovernmental Panel on Climate Change (IPCC) to reach carbon neutrality is discussed along with pathways to decarbonize the energy sector in Qatar. Next, emerging CO2 removal technologies, including physical absorption using ionic liquids, chemical looping, and cryogenics, are explored and analyzed regarding their advancement and limitations, CO2 purity, scalability, and prospects. The advantages, limitations, and efficiency of the CO2 conversion technology to value-added products are grouped into chemical (plasma catalysis, electrochemical, and photochemical) and biological (photosynthetic and non-photosynthetic). The paper concludes by analyzing pathways to decarbonize the energy sector in Qatar via coupling CCC technologies for low-carbon hydrogen, highlighting the challenges and research gaps. Other Information Published in: Journal of Cleaner Production License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jclepro.2024.141506